Self-Esteem Matters: Examining its Impact on Academic Achievement in the Context of Gender and Age Diversity in Higher Education - Abuzar, Muhammad; Purwandari, Eny (Universitas Djuanda, 2024)
Self-esteem plays a crucial role in shaping academic achievement among university students. This study investigates how self-esteem, gender, and age influence academic performance, particularly within the Indonesian context. Despite extensive global research, there needs to be more understanding of these dynamics among Indonesian university students. The study explores the relationships between self-esteem, gender, age, and academic achievement, identifying significant predictors and differences. A quantitative survey design was employed to gather data from 309 students across 12 Central Java, Indonesia universities. Data collection was executed through online surveys distributed via WhatsApp and Facebook. Data analysis was performed using Pearson correlation and multiple regression techniques with SPSS. The findings confirm that self-esteem significantly impacts academic achievement, establishing it as a strong predictor of academic success. While gender differences in self-esteem were notable, age did not significantly affect self-esteem. Interestingly, no significant gender gaps in academic performance were observed, though academic achievement varied across age groups. These conclusions suggest that enhancing self-esteem could improve academic outcomes. This research contributes to the global understanding of self-esteem dynamics, emphasizing the need for targeted interventions in educational settings. The insights gained can inform educators and policymakers in developing strategies to support students' academic success in Indonesia.